Repeated Iron–Soot Exposure and Nose-to-brain Transport of Inhaled Ultrafine Particles. (January 2018) - Hopkins, Laurie E.; Laing, Emilia A.; Peake, Janice L.; Uyeminami, Dale; Mack, Savannah M.; Li, Xueting; Smiley-Jewell, Suzette; Pinkerton, Kent E.
Particulate exposure has been implicated in the development of a number of neurological maladies such as multiple sclerosis, amyotrophic lateral sclerosis, Alzheimer's disease, and idiopathic Parkinson's disease. Only a few studies have focused on the olfactory pathway as a portal through which combustion-generated particles may enter the brain. The primary objective of this study was to define the deposition, uptake, and transport of inhaled ultrafine iron–soot particles in the nasal cavities of mice to determine whether combustion-generated nanoparticles reach the olfactory bulb via the olfactory epithelium and nerve fascicles. Adult female C57B6 mice were exposed to iron–soot combustion particles at a concentration of 200 μg/m 3, which included 40 μg/m 3 of iron oxide nanoparticles. Mice were exposed for 6 hr/day, 5 days/week for 5 consecutive weeks (25 total exposure days). Our findings visually demonstrate that inhaled ultrafine iron–soot reached the brain via the olfactory nerves and was associated with indicators of neural inflammation.